Prevalence and factors influencing long COVID among primary healthcare workers after epidemic control policy adjustment in Jiangsu, China - Hualing Chen; Yongkang Qian; Beier Lu; Rongji Ma; Pengcheng Miao; Mingwang Fu; Haijian Guo; Ya Shen; Zhengkai Shen; Yan Li; Biyun Xu; Yongjie Zhang; et al. (BMC Infectious Diseases, 2024)
Abstract Objective The persistent symptoms arising from COVID-19 infection pose a substantial threat to patients’ health, carrying significant implications. Amidst the evolving COVID-19 control strategies in China, healthcare workers (HCWs) endure considerable stress. This study aims to evaluate the prevalence of long COVID infections and their influencing factors among primary HCWs after epidemic control policy adjustment in Jiangsu. Methods A self-designed questionnaire was administered through on-site surveys among primary HCWs in five counties and districts within Jiangsu Province from July 4 to July 20, 2023. Logistic regression analysis was employed to identify factors associated with long COVID. Results The prevalence of long COVID among primary HCWs stood at 12.61%, with a 95% confidence interval (CI) of 11.67-13.55%. Among those affected, the most common long COVID symptoms were hypomnesia (4.90%, 95%CI: 4.29-5.51%), sleep difficulties (2.73%, 95%CI: 2.27-3.19%), fatigue (2.35%, 95%CI: 1.92-2.78%), disturbances in the reproductive system (1.93%, 95%CI: 1.54-2.32%), hair loss (1.85%, 95%CI: 1.47-2.23%), and myalgia/arthralgia (1.51%, 95%CI: 1.16-1.86%). Multivariate logistic regression revealed that older age groups (30–45 years (adjusted odds ratio (aOR) = 1.93, 95%CI: 1.44–2.58), 45–60 years (aOR = 2.82, 95%CI: 2.07–3.84)), females (aOR = 1.26, 95%CI: 1.03–1.55), and higher work stress (high stress (aOR = 1.52, 95%CI: 1.24–1.86), extremely high stress (aOR = 1.37, 95%CI: 1.03–1.82)) were more prone to long COVID. Conversely, individuals with educational attainment below the bachelor’s degree (aOR = 0.67, 95%CI: 0.55–0.82) and those who received four or more doses of the COVID-19 vaccine (aOR = 0.55, 95%CI: 0.33–0.92) were at a reduced risk. Conclusion This study investigates the prevalence of long COVID among primary HCWs and identifies key influencing factors. These findings are crucial for assisting in the early identification of COVID-19 patients at risk for long-term complications, developing targeted interventions aimed at optimizing healthcare resource allocation and enhancing the work conditions and quality of life of HCWs. To mitigate the prevalence of long COVID, healthcare providers and local authorities should implement effective measures, such as optimizing work-rest schedules and actively advocating for vaccination.